Integrative systematic studies on tardigrades from Antarctica identify new genera and new species within Macrobiotoidea and Echiniscoidea - VECCHI, MATTEO; CESARI, Michele; BERTOLANI, Roberto; Jonsson, K. Ingemar; REBECCHI, Lorena; GUIDETTI, Roberto (Invertebrate Systematics, 2016)
Tardigrades represent one of the most abundant groups of Antarctic metazoans in terms of abundance and diversity, thanks to their ability to withstand desiccation and freezing; however, their biodiversity is underestimated. Antarctic tardigrades from Dronning Maud Land and Victoria Land were analysed from a morphological point of view with light microscopy and scanning electron microscopy, and from a molecular point of view using two genes (18S, 28S) analysed in Bayesian inference and maximum-likelihood frameworks. In addition, indel-coding datasets were used for the first time to infer tardigrade phylogenies. We also compared Antarctic specimens with those from Italy and Greenland. A combined morphological and molecular analysis led to the identification of two new evolutionary lineages, for which we here erect the new genera Acanthechiniscus, gen. nov. (Echiniscidae, Echiniscoidea) and Mesobiotus, gen. nov. (Macrobiotidae, Macrobiotoidea). Moreover, two species new to science were discovered: Pseudechiniscus titianae, sp. nov. (Echiniscidae : Echiniscoidea) and Mesobiotus hilariae, sp. nov. (Macrobiotidae : Macrobiotoidea). This study highlights the high tardigrade diversity in Antarctica and the importance of an integrated approach in faunal and taxonomic studies.